Russian Federation Financial Sector Assessment Program : Insurance Core Principles Assessment - World Bank (World Bank, Washington, DC, 2016)
With about RUB 988bn (USD 26bn) in gross premium written, in 2014, the Russian insurance industry ranked 27th in the world. Non-life insurance premium accounted for 89 percent of GPW while life insurance for only 11 percent. In 2015, the industry also faced with the consequences of the Western economic sanctions which effectively closed access to the high quality Western reinsurance capacity for the Russian insurers that provide coverage for 1500 large Russian companies which were put on the sanctions list. In the past, the Western reinsurers provided over 80 percent of reinsurance capacity for such risks. In the case of Russia, the main objective of insurance supervision is to ensure that insurers fully comply with core regulatory norms fixed by the law in the following four areas of insurance operations: (a) solvency (capital adequacy); (b) insurance reserves; (c) assets covering own funds; and (d) assets covering reserves. The objective of off-site and onsite supervision is restricted to ensuring compliance of insurers with these four regulatory norms. In this context, the resources of the insurance supervisor are by and large dedicated towards meeting this objective. While the dispersion of insurance supervisory functions among numerous CBR departments with various reporting lines carries certain advantages (such as a reduced potential for the conflict of interest), it also has a potential for major drawbacks. These include the potential for (a) insufficient coordination among different departments, (b) shortage of necessary insurance expertise within departments universally dealing with a wide range of financial services, and (c) impaired ability of the regulator as a whole to systematically detect problems with compliance in such a technically complex industry as insurance at an early stage.